Psychology and rurality: reflections for the training in psychology - Silva, Kátya de Brito e (2019)
Rural contexts are a new field of practice for psychologists. However, the relationship between psychology and the rural still is not close enough. Psychologists’ place in this context, therefore, is still configuring itself. Considering this reality, this essay, developed through a theoretical research, aims to discuss broadly the possibilities of incorporation of the rural in Psychology courses. It is understood that the challenge is to develop training in psychology that is dedicated to clarify theoretical and practical bases that can guide techniques and ethical issues of the rural context, understanding that the qualification in this field does not involve only technical aspects but also ethical-political commitment.